Leonard Cohen: The Modern Troubadour (American & British Studies Annual, 2016)
The following essay portrays parallels between the work of a contemporary singer-songwriter and author Leonard Cohen and the medieval Occitan troubadours. The main focus is put on the importance of the feminine character in their works. This character is often discouraging to any close intimacies – as far as the world of literature is concerned – but the singers are subjected / subject themselves to persistence in its worship. The paper does not want to prove any direct relatedness, but to highlight the importance of the tradition of the troubadour song and its echoes in the popular culture as we know it.
Keywords: Leonard Cohen; song; Troubadours; poetry; medieval; woman; feminine; music; musician; religion